The number of pan-fan maps on the projective plane - Xu, Yan; Liu, Yanpei (Utilitas Mathematica, 2007)
In this paper we find an explicit expression of the number of rooted one-vertexed maps on the projective plane. Based on this result, the number of rooted pan-fan maps on the projective plane with two parameters(the valency of root-face and the size) is also provided.